2019
DOI: 10.1364/josab.36.000862
|View full text |Cite
|
Sign up to set email alerts
|

Generating Lieb and super-honeycomb lattices by employing the fractional Talbot effect

Abstract: We demonstrate a novel method for producing optically-induced Lieb and super-honeycomb lattices, by employing the fractional Talbot effect of specific periodic beam structures. Our numerical and analytical results display the generation of Lieb and super-honeycomb lattices at fractional Talbot lengths effectively and with high beam quality. By adjusting the initial phase shifts of the interfering beams, the incident periodic beam structures, as well as the lattices with broken inversion symmetry, can be constr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…For electrons with NN hopping in the HK lattice, the bands host spin-1/2 and spin-1 Dirac-Weyl fermions simultaneously [29], revealing the connection between the HK, the kagome and the honeycomb lattices. Similar band structure was found in the photonic HK lattices [30], with novel optical phenomena [31,32]. It was also demonstrated that a square-root higher-order topological insulator was realized in a two-dimensional LC circuits arranged in the HK lattice manner [33].…”
Section: Introductionsupporting
confidence: 68%
“…For electrons with NN hopping in the HK lattice, the bands host spin-1/2 and spin-1 Dirac-Weyl fermions simultaneously [29], revealing the connection between the HK, the kagome and the honeycomb lattices. Similar band structure was found in the photonic HK lattices [30], with novel optical phenomena [31,32]. It was also demonstrated that a square-root higher-order topological insulator was realized in a two-dimensional LC circuits arranged in the HK lattice manner [33].…”
Section: Introductionsupporting
confidence: 68%
“…By using Equation (6), the transverse period of the high‐order Kagome lattice is obtained as 2π and 2π/3$2\pi /\sqrt 3 $ along the x and y axes, respectively. By calculating the least common multiple of the OVL period along the two directions, [ 47 ] the total Talbot length of the high‐order Kagome lattice is obtained as ZT=4π${Z}_T = 4\pi $. Figure 7(a2) shows the corresponding Talbot carpet of the periodic beam structures.…”
Section: Resultsmentioning
confidence: 99%
“…By using Equation ( 6), the transverse period of the high-order Kagome lattice is obtained as 2𝜋 and 2𝜋∕ √ 3 along the x and y axes, respectively. By calculating the least common multiple of the OVL period along the two directions, [47] the total Talbot length of the high-order Kagome lattice is obtained as Z T = 4𝜋. transverse period of the high-order hexagonal lattice is the same as that of the high-order Kagome lattice, they exhibited the same Talbot length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ranges of the chemical potential and wavelength, the FWHM is less than 1 μm, which implies the sub-wavelength imaging in the proposed structure. However, when the length of propagation of SPPs becomes smaller than the self-imaging distance, or the loss of plasmons is high enough, the phenomena are hard to obtain [34]. It should be noted that variation of the duty cycle of graphene grating has no effect on the FWHM.…”
Section: The Fwhm Properties Of the Talbot Imagesmentioning
confidence: 99%